Power quality classification using statistical approach / Mohamad Fairuz Hassan - Hassan, Mohamad Fairuz (2008)
This paper presents a power disturbance classification using statistical method simple clustering technique that is cluster data and a conventional partitioning method that is K-Means clustering. The key idea is to compare the clustered data between these two techniques. These two approaches have the same objectives i.e. to recognize similarities, clusters and classify the disturbance to one of the identified categories. The proposed method has the potential to evaluate various power quality disturbances, such as sag, swell and notches. It also evaluates the performance of each method and discusses the strength and weaknesses of both approaches based on the simulated results.